Endocrine Regulation on Bone by Thyroid - Zhu, Siyuan; Pang, Yidan; Xu, Jun; Chen, Xiaoyi; Zhang, Changqing; Wu, Bo; Gao, Junjie (Frontiers in Endocrinology, 2022)
Background: As an endocrine organ, the thyroid acts on the entire body by secreting a series of hormones, and bone is one of the main target organs of the thyroid. Previous studies mainly focused on the effect of parathyroid hormone on bone, but the role of the thyroid in bone homeostasis cannot be ignored. Summary: This review highlights the roles of thyroid hormones and thyroid diseases in bone homeostasis. Conclusion: Thyroid hormones play significant roles in the growth and development of bone, and imbalance of thyroid hormones can impair bone homeostasis.